The causes of tooth mortality of permanent teeth in a Malaysian population - Abdul Razak, I.; Jaafar, N.; Mat Nor, G. (1989)
The reasons underlying the need for extraction of 2765 permanent teeth carried out over a 6 month period in the Out-patient Clinic in the Dental Faculty, University of Malaya, was investigated. The present study showed that dental caries (67.4) is the leading cause for extraction followed by periodontal disease (19.6). Caries accounted for the highest proportion of extractions up to the age of 50 whereas periodontal disease becomes the major factor beyond this age. The highest frequency of extractions carried out was between the ages of 21-30.